1972
DOI: 10.1177/030098587200900501
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Granulomas Associated with PAS-Positive Bodies in Brachycephalic Dogs

Abstract: Abstract. Pulmonary granulomas were incidental findings at necropsy in 18 dogs, mainly of the brachycephalic breeds. These lesions were multifocal along smaller bronchi and the subpleural tissue at the margins of lobes. The granulomatous reaction contained numerous periodic acid-Schiff (PAS)-positive bodies that histochemically had reactions suggestive of a calcium-lipid-mucopolysaccharide complex. Although the cause is not clear, the location and distribution are suggestive of an inhalation or aspiration pneu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1976
1976
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…A report of similar PAS-positive bodies in the lungs of brachycephalic dogs suggested the granulomatous response occurred as a result of inhalation or aspiration pneumonia [2]. The light microscopic appearance of the bodies seemed similar to that of those in this report, but we did not find any ultrastructural details suggestive of aspirated material.…”
Section: Discussionsupporting
confidence: 76%
“…A report of similar PAS-positive bodies in the lungs of brachycephalic dogs suggested the granulomatous response occurred as a result of inhalation or aspiration pneumonia [2]. The light microscopic appearance of the bodies seemed similar to that of those in this report, but we did not find any ultrastructural details suggestive of aspirated material.…”
Section: Discussionsupporting
confidence: 76%
“…In 1 study, lesions were predominant in brachycephalic breeds from urban settings, one-third of which had pulmonary or upper respiratory disease thought to predispose to aspiration. 5 The other study found lesions in 30 of 34 beagles exposed to airborne radon daughters (radioactive decay particles) with uranium ore dust and attributed the material to a degenerative response to injury with accumulation of endogenous secretions. 10 All but 1 of the affected EIII/JC described here were unmanipulated breeders, with no known airborne exposures (no history provided for the exception).…”
Section: Discussionmentioning
confidence: 97%
“…[4][5][6]. Interestingly, some of the smoothelin-positive intimal cells were also vimentin positive, whereas the fully differentiated contractile smooth muscle cells of the media were smoothelinþ/a-SMAþ/vimentinÀ.…”
Section: Fibromuscular Intimal Hyperplasia Of the Medium And Large Pumentioning
confidence: 99%
“…The bodies also display birefringence under polarized light. 1,4 The inciting cause and pathogenesis for this accumulation of pulmonary hyaline material is unknown, but disease is seen predominantly in older dogs and typically is considered incidental. 3 Early descriptions suggested a response to inhalation or aspiration of irritants, including uranium ore dust.…”
mentioning
confidence: 99%